Ectopic pregnancy following in vitro fertilization with embryo transfer: A single-center experience during 15 years - Ling-Yun Cheng; Pin-Yao Lin; Fu-Jen Huang; Fu-Tsai Kung; Hsin-Ju Chiang; Yu-Ju Lin; Kuo-Chung Lan (Elsevier, 2015)
Objective: Ectopic pregnancy is an obstetrical disease that is potentially associated with maternal death in the first trimester. It is one of the well-known complications following in vitro fertilization (IVF) with embryo transfer (ET). The incidence of ectopic pregnancy is estimated to be 2.1-8.6% of clinical pregnancy after IVF-ET, which is higher than natural conceptions (incidence rate 2%). This study aimed to re-evaluate the ectopic pregnancy rate in patients undergoing IVF-ET and to investigate the effects of embryo stage and frozen-thawed blastocyst transfer and ET during full bladder distention on ectopic pregnancy rate. Materials and methods: This retrospective study reviewed women who achieved a clinical pregnancy after IVF-ET at the Department of Obstetrics and Gynecology, Kaohsiung Chang Gung Memorial Hospital between 1999 and 2013. We compared ectopic pregnancy rate following Day 3 ET with Day 5 ET, and after fresh ET with thawed ET. Besides, multivariate analysis was used to clarify the factors affecting ectopic pregnancy after IVF-ET. Results: Of the total 1213 clinical pregnancies after fresh ET, 18 (1.5%) were verified as ectopic, which is similar to the rate following natural conception. The ectopic pregnancy rates were similar for Day 3 (1.2%) and Day 5 (1.7%) ETs. The incidence of ectopic pregnancy in thawed ET cycles (0.6%) was not significantly reduced than fresh ET cycles (1.5%). Tubal ET (TET) and ET under full bladder distention had a significant effect on ectopic pregnancy. Conclusion: Thawed ET was not associated with a lower incidence of ectopic pregnancy than fresh ET, and embryo stage did not affect the rate of ectopic pregnancy. In addition, TET and ET under conditions of full bladder distention may increase the ectopic pregnancy rate.